Making Sense (and Value) of Television Archives - Luca Barra; Eichner, Susanne; Marinello, Matteo; Rossi, Emiliano; Weber, Anne-Katrin (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This volume collects the proceedings of the sixteenth Media Mutations conference (University of Bologna, May 2025), which critically examined the history and transformations of television archives in the digital era. Drawing on the conclusions of the PRIN 2020 ATLas research project, the twenty-five contributions address theoretical, methodological, and operational perspectives on audiovisual archival practices, with particular attention to local television heritage, the role of digitisation and AI, questions of agency and power embedded in archival processes, and the ethical challenges of reuse and curation. Together, they argue that television archives are not inert repositories but dynamic, contested spaces where technology, memory, institutional interests, and human agency continuously intersect.